Gold cluster nano-enzyme ligand, self-assembled hydrogel and hydrogel preparation method

By using functionalized dipeptides as ligands, gold cluster nanoenzymes with assembly properties were synthesized, and the hydrogels were formed by self-assembly, the cluster agglomeration, leakage and distribution of gold cluster-based hydrogels were solved during the preparation process. The problem of unevenness has achieved uniform distribution and stability of gold cluster nanoenzymes in hydrogels, and improved its application potential in the field of tissue regeneration.

CN119462823AActive Publication Date: 2025-02-18NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411592360.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing gold cluster-based hydrogels are prone to cluster agglomeration, leakage and uneven distribution during the preparation process, and the preparation process is complex, which limits its application in the field of tissue regeneration.

Method used

Using functionalized dipeptide 9-fluorene methoxycarbonyl-phenylalanine-cysteine ​​with assembly and reduction properties as ligand, gold cluster nanoenzymes with assembly properties is synthesized in the aqueous phase by a one-step method, using Non-covalent forces such as hydrophilic effects promote the self-assembly of gold cluster structural units and form a self-assembly hydrogel of gold clusters.

Benefits of technology

The uniform distribution and stability of gold cluster nanoenzymes in hydrogels is achieved, the preparation process is simplified, and the hydrogels are given excellent biosafety and peroxidase-like activity is improved, which has improved its application in the field of tissue regeneration. potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462823A_ABST
    Figure CN119462823A_ABST
Patent Text Reader

Abstract

The invention provides a ligand for gold cluster nano-enzyme, and a method for preparing gold cluster nano-enzyme self-assembled hydrogel by using the ligand for gold cluster nano-enzyme, which comprises the following steps: synthesizing gold cluster nano-enzyme in a water phase by using the ligand for gold cluster nano-enzyme through a one-step method, adding the gold cluster nano-enzyme into a completely dissolved gel factor hot solution, and carrying out hydrothermal reaction to obtain the gold cluster nano-enzyme self-assembled hydrogel. And cooling and standing at room temperature to obtain the gold cluster nano-enzyme self-assembled hydrogel. The invention also provides the gold cluster nano enzyme self-assembled hydrogel prepared by the preparation method. The ligand for the gold cluster nano-enzyme has both reducibility and assembly performance, the method for preparing the hydrogel by using the ligand is simple and easy to implement, the reaction condition is mild, complex instruments and equipment and other cross-linking agents are not needed, the uniformity and stability of the gold cluster nano-enzyme in the hydrogel can be improved, and the preparation method is simple and easy to implement. In addition, the hydrogel is endowed with various biological properties such as excellent biological safety and peroxidase-like activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-biomaterial preparation, and in particular to a gold cluster nano-enzyme-based hydrogel with self-assembly performance, a ligand thereof and a preparation method thereof. Background Art

[0002] Infectious tissue defects are usually accompanied by a variety of problems such as bacterial infection and excessive inflammation, which seriously hinder the tissue repair and regeneration process. Among many biomaterials, multifunctional hydrogels have become ideal materials for promoting infectious tissue regeneration due to their good biocompatibility, biodegradability and extracellular matrix-like three-dimensional structure. However, most multifunctional hydrogels are difficult to meet clinical needs due to their single biological function and complex preparation process. Therefore, it is urgent to develop a new type of hydrogel that can meet the needs of both process simplicity and multifunctionality.

[0003] In recent years, with the development of nanotechnology and nanomaterials, combining nanomaterials with hydrogels has become a new strategy for constructing multifunctional hydrogels. Among them, gold clusters have been widely studied in the fields of disease diagnosis and treatment and tissue regeneration due to their excellent pharmacokinetic properties, good biocompatibility and enzyme-like catalytic activity. In particular, gold clusters with peroxidase-like catalytic properties have shown significant effects in efficient antibacterial and anti-infection. In addition, the surface ligands of gold clusters are rich and adjustable, and their physicochemical properties and biological functions can be precisely controlled by designing and screening suitable ligand structures. Therefore, gold clusters have unique advantages and great potential in constructing multifunctional hydrogels.

[0004] At present, researchers generally encapsulate gold clusters as independent components into the three-dimensional network structure of hydrogels by in situ coating. This method is easy to operate, but it is prone to problems such as agglomeration, leakage and uneven distribution of gold clusters. In addition, molecules with cross-linking functions can be used as functional ligands to modify the surface of gold clusters, and physical and chemical cross-linking reactions between functionalized ligands and other polymers can be used to construct gold cluster composite hydrogels. This method can prevent the leakage of gold clusters and improve the mechanical properties of hydrogels to a certain extent. However, the complexity of the preparation process and potential biosafety risks limit its application in the field of tissue regeneration.

[0005] Therefore, in order to further improve the stability, uniformity and ease of preparation of gold cluster-based hydrogels, it is urgent to develop more efficient hydrogel preparation strategies. Summary of the invention

[0006] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a method for synthesizing gold clusters using functionalized dipeptides with assembly ability and multiple biological properties as ligands, so that the prepared gold clusters have excellent assembly performance, and use non-covalent forces such as hydrophilic and hydrophobic interactions as the main driving force to promote the self-assembly process of gold cluster structural units to obtain gold cluster self-assembled hydrogels. The reaction conditions are mild and the operation is simple. The prepared gold cluster self-assembled hydrogel also exhibits excellent biocompatibility and peroxidase-like properties of the gold cluster nanozyme self-assembled hydrogel and its preparation method.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a ligand for gold cluster nanozyme, wherein the ligand for gold cluster nanozyme has both reducing and assembly properties, and the ligand structure is a functionalized dipeptide of 9-fluorenylmethoxycarbonyl-phenylalanine-cysteine, and the molecular structure is:

[0008]

[0009] The present invention also provides a method for preparing a gold cluster nanozyme self-assembly hydrogel using the ligand, comprising the following steps:

[0010] Step 1: using the gold cluster nanozyme ligand, synthesizing the gold cluster nanozyme in an aqueous phase through a one-step method;

[0011] Step 2: Add the gold cluster nanozyme to the completely dissolved hot solution of the gel factor, and after cooling and standing at room temperature, the gold cluster nanozyme self-assembled hydrogel is obtained.

[0012] Further, the one-step method described in step 1 is specifically as follows:

[0013] Adding a sodium hydroxide aqueous solution to the aqueous solution of the ligand for the gold cluster nanozyme to obtain a completely dissolved ligand solution; then, adding a chloroauric acid solution to the ligand solution, mixing and stirring evenly, and reacting under the conditions of a heating temperature of 40 to 90° C. and a heating time of 10 to 18 hours to obtain a gold cluster nanozyme modified with a ligand for the gold cluster nanozyme having assembly performance;

[0014] Among them, the molar ratio of the gold cluster nanozyme ligand to chloroauric acid is 1.5 to 1.9:1.

[0015] Furthermore, the concentration of the sodium hydroxide aqueous solution is 9.5-15 mmol / L, so that the one-step method is carried out under alkaline conditions with a pH value of 9-12.

[0016] Further, after adding the chloroauric acid solution to the ligand solution, specifically:

[0017] Under room temperature, stirring at a speed of 500 rpm for at least 10 to 20 minutes, then setting the temperature of the reaction system to 40 to 90° C., and stirring at a speed of 500 rpm for 10 to 18 hours to obtain a light yellow final reaction solution;

[0018] The final reaction solution was centrifuged at a speed of 10000-12500 rpm for 10-20 minutes to remove the precipitate in the solution, and the product was further purified by ultrafiltration centrifugation 3-6 times using an ultrafiltration centrifuge tube with a cutoff molecular weight of 10 kDa. The purified gold cluster nanozyme was concentrated by vacuum concentration to increase its concentration to 10-24 times of the original, and then placed at 4°C for use.

[0019] Furthermore, the structure of the gel factor described in step 2 is 9-Fmoc-phenylalanine.

[0020] Furthermore, the step 2 is specifically as follows:

[0021] The gelling factor powder is added to a phosphate buffer solution with a concentration of 50 to 200 mmol / L, and then heated at a temperature of 50 to 80° C. for 10 to 30 minutes to fully dissolve the gelling factor powder to obtain the gelling factor hot solution, and then a gold cluster nanozyme aqueous solution with a concentration of 8 to 17 mg / mL is added to the gelling factor hot solution, mixed, and cooled and allowed to stand at room temperature for 6 to 24 hours to obtain the gold cluster nanozyme self-assembled hydrogel;

[0022] Among them, the mass ratio of gel factor and gold cluster nanozyme in the gold cluster nanozyme self-assembled hydrogel is 3-5 mg: 0.8-1.7 mg.

[0023] The present invention also provides a gold cluster nanozyme self-assembled hydrogel prepared by the method, wherein the gold cluster nanozyme participates in the construction of the hydrogel fiber structure in an assembled manner, and the gold cluster nanozyme is uniformly distributed in the fiber network structure of the hydrogel.

[0024] The beneficial effects of the present invention are as follows: the present invention designs a functionalized dipeptide having both assembly and reduction properties and multiple biological properties: 9-fluorenylmethoxycarbonyl-phenylalanine-cysteine ​​(Fmoc-FC) is used as a ligand to synthesize a gold cluster nanozyme having assembly properties and peroxidase-like catalytic properties; the 9-fluorenylmethoxycarbonyl group in the ligand structure and the aromatic group on the phenylalanine side chain enable the gold cluster nanozyme to participate in the assembly process of the hydrogel fiber structure by utilizing π-π stacking and hydrophobic interactions, and be evenly distributed on the formed fiber structure, thereby forming a new type of gold cluster nanozyme self-assembly hydrogel.

[0025] This preparation method is simple and easy, with mild reaction conditions and no need for complex instruments and other cross-linking agents. It can not only improve the uniformity and stability of gold cluster nanozymes in hydrogels, but also give hydrogels excellent biosafety and peroxidase-like activity and other biological properties.

[0026] The gold cluster nanozyme (Fmoc-FC-AuNCs) prepared by the method of the present invention has excellent peroxidase-like activity under acidic conditions, and the phenylalanine in the gel factor (Fmoc-F) in the hydrogel structure can dissociate H in a neutral environment. + , further providing an acidic microenvironment for Fmoc-FC-AuNCs to enhance their enzyme-like catalytic performance, allowing the hydrogel to break through the limitations of environmental factors such as pH on the enzyme-like activity of Fmoc-FC-AuNCs, and still exhibit significant enzyme-like activity under near-neutral and other physiological environments, which is conducive to its wide application in biomedical fields such as tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a transmission electron microscope image of Fmoc-FC-AuNCs of the present invention;

[0028] Figure 2 It is the Fourier transform infrared absorption spectrum of the Fmoc-FC ligand and Fmoc-FC-AuNCs nanozyme of the present invention;

[0029] Figure 3 It is the transmission electron microscope image and element distribution map of the gold cluster nanozyme hydrogel of the present invention,

[0030] Among them, Figure (a) is a transmission electron microscope image and energy spectrum scanning area of ​​the hydrogel three-dimensional fiber structure, and Figures (b), (c), (d), (e) and (f) are distribution diagrams of C, N, O, S and Au elements;

[0031] Figure 4 It is the characterization of the peroxidase-like catalytic activity of the Fmoc-FC-AuNCs and gold cluster nanozyme self-assembled hydrogel of the present invention.

[0032] Among them, Figure (a) is the characterization of the catalytic activity when the pH of the reaction environment is 6.0, and Figure (b) is the characterization of the catalytic activity when the pH of the reaction environment is 7.4. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] At present, hydrogels composited with functional nanomaterials have multiple advantages in promoting the repair and regeneration of infectious tissues, but the complex preparation process and limited biological functions affect their further application.

[0035] Therefore, the present invention designs a functionalized dipeptide Fmoc-FC with excellent assembly performance and multiple biological properties, and uses it as a ligand to prepare Fmoc-FC-AuNCs nanozyme with assembly properties through a one-step method, and further constructs a new type of gold cluster nanozyme self-assembly hydrogel under the synergistic effect of the gel factor Fmoc-F.

[0036] On the one hand, this preparation method is independent of other chemical cross-linking agents, allowing the gold cluster nanozymes to participate in the construction of the hydrogel fiber structure in an assembly manner, simplifying the preparation process of the gold cluster-based hydrogel and ensuring the stable and uniform distribution of the gold cluster nanozymes in the hydrogel; on the other hand, based on the intrinsic peroxidase-like activity of Fmoc-FC-AuNCs and the unique amphiphilicity of its ligand and gel factor structure, the prepared gold cluster nanozyme self-assembled hydrogel not only has good biocompatibility, but also exhibits excellent enzyme-like catalytic activity and great anti-infection application prospects.

[0037] In order to achieve the above object, the present invention provides the following specific implementation methods:

[0038] Example 1: A ligand for a gold cluster nanozyme, wherein the ligand for the gold cluster nanozyme has both reducing and assembly properties, and the ligand structure is a functionalized dipeptide of 9-fluorenylmethoxycarbonyl-phenylalanine-cysteine, and the molecular structure is:

[0039]

[0040] Example 2: A method for preparing a gold cluster nanozyme self-assembled hydrogel using the ligand provided in Example 1, comprising the following steps:

[0041] Step 1: using the gold cluster nanozyme ligand, synthesizing the gold cluster nanozyme in an aqueous phase by a one-step method, specifically:

[0042] Adding a sodium hydroxide aqueous solution to the aqueous solution of the ligand for the gold cluster nanozyme, wherein the concentration of the sodium hydroxide aqueous solution is 9.5 to 15 mmol / L, so that the reaction is carried out under alkaline conditions with a pH value of 9 to 12, and a completely dissolved ligand solution is obtained; then, adding a chloroauric acid solution to the ligand solution, stirring at a speed of 500 rpm for at least 10 to 20 minutes at room temperature, then setting the temperature of the reaction system to 40 to 90° C., and stirring at a speed of 500 rpm for 10 to 18 hours to obtain a light yellow final reaction solution;

[0043] The final reaction solution is centrifuged at a speed of 10000-12500 rpm for 10-20 minutes to remove the precipitate in the solution, and then the product is further purified by ultrafiltration centrifugation 3-6 times using an ultrafiltration centrifuge tube with a cut-off molecular weight of 10 kDa. The purified gold cluster nanozyme is concentrated by vacuum concentration to increase the concentration to 10-24 times of the original concentration, and then placed at 4°C for standby use, thereby obtaining a gold cluster nanozyme modified with a ligand for a gold cluster nanozyme with assembly performance;

[0044] Among them, the molar ratio of the gold cluster nanozyme ligand to chloroauric acid is 1.5 to 1.9:1.

[0045] Step 2: Add gel factor powder to a phosphate buffer with a concentration of 50 to 200 mmol / L, wherein the structure of the gel factor is 9-fluorenylmethoxycarbonyl-phenylalanine; then heat at a temperature of 50 to 80°C for 10 to 30 minutes to fully dissolve the gel factor powder to obtain the gel factor hot solution, and then add a gold cluster nanozyme aqueous solution with a concentration of 8 to 17 mg / mL to the gel factor hot solution, mix well, and cool and stand at room temperature for 6 to 24 hours to obtain the gold cluster nanozyme self-assembled hydrogel;

[0046] Among them, the mass ratio of gel factor and gold cluster nanozyme in the gold cluster nanozyme self-assembled hydrogel is 3-5 mg: 0.8-1.7 mg.

[0047] Example 3: A gold cluster nanozyme self-assembled hydrogel prepared by the method of Example 2, wherein the gold cluster nanozyme participates in the construction of the hydrogel fiber structure in an assembled manner, and the gold cluster nanozyme is uniformly distributed in the fiber network structure of the hydrogel.

[0048] In order to further explain the present invention and its effects, the present invention provides the following specific experimental examples:

[0049] Specific experimental example 1:

[0050] 1) Preparation of gold cluster nanozymes: A functionalized dipeptide with a structure of 9-fluorenylmethoxycarbonyl-phenylalanine-cysteine ​​(Fmoc-FC) was used as a ligand, and a chloroauric acid solution was reduced in an aqueous phase by a one-step method to obtain Fmoc-FC modified gold cluster nanozymes (Fmoc-FC-AuNCs). Specifically, 16.8 mg of Fmoc-FC was dissolved in 0.34 mL of ultrapure water, and then 12.6 mL of sodium hydroxide aqueous solution (15 mmol / L) was added to the Fmoc-FC aqueous solution. After the solution was completely clarified by ultrasound, a chloroauric acid solution (1 mL, 20 mmol / L) was added and stirred at 500 rpm for 10 minutes at room temperature. The temperature of the reaction system was then set to 50°C, and stirred at 500 rpm for 10 hours to obtain a light yellow final reaction solution. The solution was then centrifuged at 12,500 rpm for 15 minutes to remove the precipitate in the solution, and the product was further purified by ultrafiltration centrifugation six times using an ultrafiltration centrifuge tube with a cutoff molecular weight of 10 kDa. The purified gold cluster nanozyme was concentrated by vacuum concentration to increase its concentration to 24 times the original concentration, and then placed at 4°C for use.

[0051] 2) Preparation of gold cluster nanozyme self-assembled hydrogel: Take 4 mg of 9-fluorenylmethoxycarbonyl-phenylalanine (Fmoc-F) powder and add it to 0.9 mL of phosphate buffer (50 mmol / L, pH 7.4), then heat it at 80°C for 20 minutes to fully dissolve Fmoc-F, and then add Fmoc-FC-AuNCs aqueous solution (0.1 mL, 17 mg / mL) to the Fmoc-F hot solution. After mixing, cool and stand at room temperature for 6 hours to obtain the gold cluster nanozyme self-assembled hydrogel.

[0052] Specific experimental example 2:

[0053] The same as the specific experimental example 1, except that in step 1), 16.8 mg of Fmoc-FC was dissolved in 0.34 mL of ultrapure water, and then 12.6 mL of sodium hydroxide aqueous solution (9.5 mmol / L) was added to the Fmoc-FC aqueous solution, and after the solution was completely clarified by ultrasound, chloroauric acid solution (1 mL, 20 mmol / L) was added and stirred at room temperature at a speed of 500 rpm for 10 minutes.

[0054] When the concentration of the sodium hydroxide aqueous solution is not within the range of 9.5 to 15 mmol / L, Fmoc-FC cannot be completely dissolved after ultrasound, and thus Fmoc-FC-AuNCs cannot be prepared; when the concentration of the sodium hydroxide aqueous solution is 15 mmol / L, more stable Fmoc-FC-AuNCs with higher comprehensive performance can be obtained.

[0055] Specific experimental example 3:

[0056] The same as the specific experimental example 1, except that in step 1), 14.7 mg of Fmoc-FC was dissolved in 0.34 mL of ultrapure water, and then 12.6 mL of sodium hydroxide aqueous solution (15 mmol / L) was added to the Fmoc-FC aqueous solution.

[0057] Specific experimental example 4:

[0058] The same as Specific Experimental Example 3, except that in step 1), 18.6 mg of Fmoc-FC was dissolved in 0.34 mL of ultrapure water, and then 12.6 mL of sodium hydroxide aqueous solution (15 mmol / L) was added to the Fmoc-FC aqueous solution.

[0059] The synthesis conditions of Fmoc-FC-AuNCs were optimized by adjusting the molar ratio of Fmoc-FC and chloroauric acid. When the molar ratio of Fmoc-FC and chloroauric acid was 1.7:1, Fmoc-FC-AuNCs with higher preparation efficiency and higher performance could be obtained.

[0060] Specific experimental example 5:

[0061] The same as the specific experimental example 1, except that in step 1), the temperature of the reaction system is then set to 40° C., and stirred at a rotation speed of 500 rpm for 10 hours to obtain a light yellow final reaction solution.

[0062] Specific experimental example 6:

[0063] The same as the specific experimental example 5, except that in step 1), the temperature of the reaction system is then set to 90° C., and stirred at a rotation speed of 500 rpm for 10 hours to obtain a light yellow final reaction solution.

[0064] When the temperature of the reaction system is not within the range of 40-90 °C, stable Fmoc-FC-AuNCs cannot be synthesized.

[0065] Specific experimental example 7:

[0066] The same as the specific experimental example 1, except that in step 1), the temperature of the reaction system was then set to 50° C., and stirred at a rotation speed of 500 rpm for 15 hours to obtain a light yellow final reaction solution.

[0067] Specific experimental example 8:

[0068] The same as the specific experimental example 7, except that in step 1), the temperature of the reaction system was then set to 50° C., and stirred at a rotation speed of 500 rpm for 18 hours to obtain a light yellow final reaction solution.

[0069] The stability and fluorescence intensity of Fmoc-FC-AuNCs will show a trend of first increasing and then decreasing with the increase of synthesis time. When the synthesis time is 10 hours, the preparation process can be further simplified and the efficiency can be improved while making the gold clusters have higher performance and stability.

[0070] Specific experimental example 9:

[0071] The same as the specific experimental example 1, except that in step 2), 3 mg of Fmoc-F powder was added to 0.9 mL of phosphate buffer (50 mmol / L, pH 7.4), and then heated at 80° C. for 20 minutes to fully dissolve Fmoc-F.

[0072] Specific experimental example 10:

[0073] The same as the specific experimental example 9, except that in step 2), 5 mg of Fmoc-F powder was added to 0.9 mL of phosphate buffer (50 mmol / L, pH 7.4), and then heated at 80° C. for 20 minutes to fully dissolve Fmoc-F.

[0074] Specific experimental example 11:

[0075] The same as the specific experimental example 1, except that in step 2), Fmoc-FC-AuNCs aqueous solution (0.1 mL, 8 mg / mL) was then added to the Fmoc-F hot solution, mixed and then cooled and allowed to stand at room temperature for 6 hours to obtain the gold cluster nanozyme self-assembled hydrogel.

[0076] Specific experimental example 12:

[0077] The same as specific experimental example 11, except that in step 2), Fmoc-FC-AuNCs aqueous solution (0.1 mL, 11 mg / mL) was then added to the Fmoc-F hot solution, mixed and cooled at room temperature for 6 hours to obtain the gold cluster nanozyme self-assembled hydrogel.

[0078] By adjusting the ratio of Fmoc-F and Fmoc-FC-AuNCs in the hydrogel system, the preparation conditions of the hydrogel were optimized. When the concentrations of Fmoc-F and Fmoc-FC-AuNCs were 4 mg / mL and 1.7 mg / mL, respectively, a gold cluster nanozyme self-assembled hydrogel with faster gelation rate and higher stability could be obtained.

[0079] The gold cluster nanozyme solution prepared by the present invention is a light yellow liquid. Figure 1 is a transmission electron microscope photo of Fmoc-FC-AuNCs prepared in specific experimental example 1 of the present invention. Figure 1It can be seen that it has uniform size and good dispersibility, and the average particle size is 2.19 nm.

[0080] Figure 2 1 is a Fourier transform infrared absorption spectrum of the ligand Fmoc-FC selected by the present invention and the Fmoc-FC-AuNCs nanozyme prepared in specific experimental example 1. Figure 2 As shown, compared with the pure Fmoc-FC ligand, the Fmoc-FC-AuNCs has a -1 The characteristic peak of thiol (-SH) disappeared while the characteristic peaks of other functional groups in the ligand still existed, indicating that Fmoc-FC-AuNCs were successfully prepared and the structure of the ligand with assembly performance did not change.

[0081] Figure 3 is a transmission electron microscopy image of the Fmoc-FC-AuNCs nanozyme hydrogel prepared in the specific experimental example 1 of the present invention, wherein Figure 3 (a) is the energy spectrum scanning area of ​​the sample, Figure 3 (b), (c), (d), (e) and (f) are the distribution diagrams of C, N, O, S and Au elements, respectively. It can be seen from the figure that the hydrogel forms a loose and porous three-dimensional fiber network structure, and the S and Au elements are evenly distributed on the fiber structure, indicating that Fmoc-FC-AuNCs are evenly distributed in the fiber network structure of the hydrogel.

[0082] Figure 4 The peroxidase-like catalytic activity of the Fmoc-FC-AuNCs nanozyme and the Fmoc-FC-AuNCs nanozyme hydrogel prepared in the specific experimental example 1 of the present invention is characterized, wherein Figure (a) is the catalytic activity characterization when the reaction environment pH is 6.0, and Figure (b) is the catalytic activity characterization when the reaction environment pH is 7.4. The peroxidase-like properties of different materials were detected using the substrate o-phenylenediamine (OPD). 100 μL of Fmoc-FC-AuNCs solution or Fmoc-FC-AuNCs hydrogel (Fmoc-FC-AuNCs final concentration of 560 μg / mL), 25 μL of OPD solution (final concentration 12.5 mmol / L) and 25 μL of H were added to 150 μL of phosphate buffer with pH values ​​of 6.0 and 7.4, respectively. 2 O 2 The solution (final concentration 40 mmol / L) was incubated at 37 °C for 30 min, and then the absorption spectra of different samples were recorded using UV-visible absorption spectroscopy. Fmoc-FC-AuNCs can catalyze the decomposition of H 2 O 2 Hydroxyl radicals are generated, causing OPD to be oxidized into a yellow oxidation product with a distinct characteristic peak at 450nm. Figure 4 It can be seen that Fmoc-FC-AuNCs have excellent peroxidase-like activity under acidic conditions ( Figure 4 (a)), and Fmoc-FC-AuNCs nanozyme hydrogel can provide an acidic microenvironment for Fmoc-FC-AuNCs, significantly enhancing the peroxidase-like activity of the hydrogel in a neutral environment ( Figure 4 (b)).

[0083] The present invention uses Fmoc-FC as a ligand to synthesize gold cluster nanozymes (Fmoc-FC-AuNCs) with assembly properties, and further constructs gold cluster nanozyme self-assembly hydrogels through non-covalent interactions such as hydrophilic and hydrophobic interactions and π-π stacking interactions. Using functionalized dipeptides with assembly properties as ligands can not only accurately regulate the biological properties of gold clusters, but also enable the synthesized gold cluster nanozymes to participate in the efficient construction of multifunctional hydrogel networks in the form of structural units.

[0084] The present invention is different from traditional preparation strategies of gold cluster-based hydrogels such as in situ coating and chemical cross-linking. By designing and selecting suitable ligand structures, gold clusters can participate in the construction of hydrogel networks in the form of assembly, thereby effectively avoiding unfavorable factors such as easy leakage and uneven distribution of gold cluster nanozymes and potential biosafety risks.

[0085] The ligands designed and the gel factors selected in the present invention have good biocompatibility and multiple potential biological properties, and the preparation method is simple to operate, the reaction conditions are mild, and no complicated instruments and equipment are required. It can not only simplify the preparation process of gold cluster-based hydrogels and improve their preparation efficiency, but also improve the stability and uniformity of gold clusters in hydrogels. The prepared gold cluster nanozyme self-assembled hydrogel has good biocompatibility and excellent enzyme-like activity, and is expected to kill bacteria by in-situ catalytic generation of hydroxyl free radicals, and has great application potential in the field of infectious tissue repair and regeneration.

[0086] The above description is only a preferred specific experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ligand for a gold cluster nanozyme, characterized in that: The gold cluster nanozyme ligand has both reducing and assembling properties, and the ligand structure is a functionalized dipeptide of 9-fluorenylmethoxycarbonyl-phenylalanine-cysteine, and the molecular structure is:

2. A method for preparing a gold cluster nanozyme self-assembled hydrogel using the ligand according to claim 1, characterized in that: The following steps are involved: Step 1: using the gold cluster nanozyme ligand, synthesizing the gold cluster nanozyme in an aqueous phase through a one-step method; Step 2: Add the gold cluster nanozyme to the completely dissolved hot solution of the gel factor, and after cooling and standing at room temperature, the gold cluster nanozyme self-assembled hydrogel is obtained.

3. The method for preparing the gold cluster nanozyme self-assembled hydrogel according to claim 2, characterized in that: The one-step method described in step 1 is specifically: Adding a sodium hydroxide aqueous solution to the aqueous solution of the ligand for the gold cluster nanozyme to obtain a completely dissolved ligand solution; then, adding a chloroauric acid solution to the ligand solution, mixing and stirring evenly, and reacting under the conditions of a heating temperature of 40 to 90° C. and a heating time of 10 to 18 hours to obtain a gold cluster nanozyme modified with a ligand for the gold cluster nanozyme; Among them, the molar ratio of the gold cluster nanozyme ligand to chloroauric acid is 1.5 to 1.9:

1.

4. The method for preparing the gold cluster nanozyme self-assembled hydrogel according to claim 3, characterized in that: The concentration of the sodium hydroxide aqueous solution is 9.5-15 mmol / L, so that the one-step method is carried out under alkaline conditions with a pH value of 9-12.

5. The method for preparing the gold cluster nanozyme self-assembled hydrogel according to claim 3, characterized in that: After adding the chloroauric acid solution to the ligand solution, specifically: Under room temperature, stirring at a speed of 500 rpm for at least 10 to 20 minutes, then setting the temperature of the reaction system to 40 to 90° C., and stirring at a speed of 500 rpm for 10 to 18 hours to obtain a light yellow final reaction solution; The final reaction solution was centrifuged at a speed of 10000-12500 rpm for 10-20 minutes to remove the precipitate in the solution, and the product was further purified by ultrafiltration centrifugation 3-6 times using an ultrafiltration centrifuge tube with a cutoff molecular weight of 10 kDa. The purified gold cluster nanozyme was concentrated by vacuum concentration to increase its concentration to 10-24 times of the original, and then placed at 4°C for use.

6. The method for preparing the gold cluster nanozyme self-assembled hydrogel according to claim 2, characterized in that: The structure of the gel factor described in step 2 is 9-Fmoc-phenylalanine.

7. The method for preparing the gold cluster nanozyme self-assembled hydrogel according to any one of claims 1 to 6, characterized in that: The step 2 is specifically as follows: The gelling factor powder is added to a phosphate buffer solution with a concentration of 50 to 200 mmol / L, and then heated at a temperature of 50 to 80° C. for 10 to 30 minutes to fully dissolve the gelling factor powder to obtain the gelling factor hot solution, and then a gold cluster nanozyme aqueous solution with a concentration of 8 to 17 mg / mL is added to the gelling factor hot solution, mixed, and cooled and allowed to stand at room temperature for 6 to 24 hours to obtain the gold cluster nanozyme self-assembled hydrogel; Among them, the mass ratio of gel factor and gold cluster nanozyme in the gold cluster nanozyme self-assembled hydrogel is 3-5 mg: 0.8-1.7 mg.

8. A gold cluster nanozyme self-assembled hydrogel prepared by the method of claims 1-7, characterized in that: The gold cluster nanozyme participates in the construction of the hydrogel fiber structure in an assembly manner, and the gold cluster nanozyme is evenly distributed in the fiber network structure of the hydrogel.

Citation Information

Patent Citations

  • Renal fibrosis therapeutic drug loaded gold-nano assemble and preparation method thereof

    CN108635591A

  • Cationic dipeptide and gold hybridized microsphere and preparation method and application thereof

    CN109596690A

  • Chiral cysteine nano self-assembled antibacterial material, preparation method and application thereof

    CN112889840A

  • Nanometer liquid metal particle capable of being assembled and preparation method and application thereof

    CN113501860A

  • Dipeptide, preparation method and application thereof, metallo-beta-lactamase inhibitor and pharmaceutical composition

    CN113563415A

Cited By

  • Hypoxia response type gold-copper cluster nano-enzyme microgel as well as preparation method and application of hypoxia response type gold-copper cluster nano-enzyme microgel

    CN120022231A